Comparison of postoperative outcomes between open surgical release and ultrasound guided percutaneous release of trigger finger: a systematic review and meta-analysis - Sandaqji, Danah O.; Alzahrani, Israa A.; Alharbi, Samirah S.; Almasoud, Sharifah H.; AlMutairi, Leen O.; Alreshidi, Nawaf O.; Ghalimah, Bayan A. (International Journal of Research in Orthopaedics, 2026)
Trigger finger is a hand condition that can be treated surgically through an open procedure or ultrasound (US)-guided percutaneous release. While similar techniques differ in invasiveness, recovery time, and complication rates, our research aims to compare the clinical outcomes of both techniques, focusing on pain relief, functional recovery, and patient satisfaction. A literature search was conducted in PubMed and the Cochrane Library. Six reviewers screened titles and abstracts, resolving conflicts with a seventh, and assessed full texts for eligibility. Included studies involved adult patients treated surgically for trigger finger with reported postoperative outcomes. Data was extracted using a standardised sheet capturing study details, demographics, management approaches, outcomes, and statistical methods. Eleven studies comparing open and US-guided release were included. Pooled analysis of six studies showed no significant difference in postoperative pain visual analogue scale (VAS) score [MD: 0.04 (-0.27, 0.34), p=0.80], with substantial heterogeneity (I²=74%). Q-DASH analysis from three studies also showed no significant difference in functional outcomes [MD:-0.06 (-2.24, 2.13), p=0.96], with heterogeneity (I²=79%) resolved through sensitivity analysis. Patient satisfaction was initially similar between groups, but after removing one study, open surgery showed significantly lower odds of satisfaction compared to US-guided release [OR: 0.23 (0.08, 0.64), p=0.005]. Our meta-analysis suggests that US-guided trigger finger release appears to provide similar pain relief and functional recovery as open surgery, with greater patient satisfaction. However, study heterogeneity calls for more high-quality research to confirm these findings.